2006
DOI: 10.1108/02634500610701681
|View full text |Cite
|
Sign up to set email alerts
|

Market orientation in Nigerian companies

Abstract: PurposeTo investigate the practice of market orientation, with a specific focus on the extent to which Nigerian marketers place emphasis on the different dimensions of market orientation, customer satisfaction, competitiveness, market intelligence, and assessment of the effectiveness of the strategies adopted.Design/methodology/approachThe study uses a contextualized and literature‐based research instrument to measure the applications of market orientation “constructs” by 697 small and large manufacturing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 68 publications
3
34
1
Order By: Relevance
“…To create superior value for buyers continuously requires that a seller understand a buyers' entire value chain, not only as it is today but also as it evolves over time. This statement is consistent with hypothesized relationship (H2) between market orientation and customer consequences in this study .Osuagwu,(2006),concluded that marketing concept is concerned with customer-orientation,innovation and profit as an inducement for creating satisfied customers. ISSN 1941-899X 2014 …”
Section: Resultssupporting
confidence: 78%
“…To create superior value for buyers continuously requires that a seller understand a buyers' entire value chain, not only as it is today but also as it evolves over time. This statement is consistent with hypothesized relationship (H2) between market orientation and customer consequences in this study .Osuagwu,(2006),concluded that marketing concept is concerned with customer-orientation,innovation and profit as an inducement for creating satisfied customers. ISSN 1941-899X 2014 …”
Section: Resultssupporting
confidence: 78%
“…For practitioners, these findings suggest that organisations ought to view corporate social responsibility and market orientation as a complementary strategic choice by managers rather than as two separate strategies that compete for organisational resources. These findings are particularly important in the context of a developing economy in which practitioners might be skeptical in implementing western theories in their businesses (Osuagwu 2006;Appiah-Adu 1998). This assertion is based on the assumption that CSR hitherto was regarded as incompatible with market strategies like market orientation developing economies because of the absence of strong institutional support for CSR and the presence of weak and ineffective laws to guard against unethical practices (Atuguba and Dowuona-Hammond 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Marketing strategy is define as in a given market area, the proper allocation of resources to support enterprises to win competitive advantage. Goi (2005) define marketing strategy as the set of the marketing tools that firms use to pursue their marketing objectives in the target market; the view which was earlier expressed by (Gronroos, 1999, andOsuagwu, 2006).Therefore, the function of marketing strategy is to determine the nature, strength, direction, and interaction between the marketing mix-elements and the environmental factors in a particular situation. According to (owomoyela, et al, 2013), the aim of the development of an organization"s marketing strategy development is to establish, build, defend and maintain its competitive advantage.…”
Section: Literature Reviewmentioning
confidence: 99%